Love Me, Love Me Not: The Florenese Struggle in the Indonesian Nation State Project of Nation Unity - Tular Sudarmadi (Humaniora, 2011)
lndonesian nation state develops project of nation unity to share imagined past and to offer a future dream. In this process, the nation with its power and authority invents, reinvents and creates collective memory by attaching meaning to cultural heritage, both tangible -sacred artifacts, monuments, sites and landscapes- and intangible -national history, religious celebration, nation day commemoration and collective memory-. However, when this collective memory is associated with the cultural heritage of major ethnic group, it marginalizes, subordinates and denies the heritage of ethnic groups outside the core. In response to the state ignorance, the minor ethnic groups develop various ways to attach and include on the nation state project of nation unity. In this article I discuss the Florenese marginalize ethnic in lndonesian nation state struggle to be granting the status of homogeneity and belonging to the Indonesian nation state citizen.